2013
DOI: 10.1007/s13593-013-0182-5
|View full text |Cite
|
Sign up to set email alerts
|

Maize residues, soil quality, and wheat growth in China. A review

Abstract: Crop residue retention is a key component of sustainable cropping systems. In recent years, retention of crop residue is a means of improving soil quality and nutrient capacity and reducing the adverse effects of residue burning. Maize-wheat rotation is a major double-cropping system practiced on more than one fifth of agricultural lands worldwide. Currently, more than 50 % of maize residues are retained immediately after harvesting. In China, this practice has beneficial effects on soil properties and product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…An increase in protein content, protein yield, and amino acids like lysine, methionine (MTN), and tryptophan, might be due to the fact that crop residue retention improved microbial activity as envisaged by an increase in potassium‐solubilizing bacterial population, soil enzyme activities, and soil microbial biomass that resulted in augmenting the availability of N, P, K, and other micronutrient concentration in soil and also thereby increased absorption and assimilation of N by plants that might have encouraged the translocation of N from vegetative parts to grain which indirectly improved amino acid and protein content. [ 37,44 ] This is in consonance with the earlier findings of Kong, [ 3 ] who reported that nitrate assimilation by wheat increased protein and amino acid profile. Among different K levels, 50% RDK+KSB produced significantly higher protein content, protein yield, and amino acid content over No K and it was statistically nonsignificant with 100 and 150% RDK (Tables 6 and 7), and is in accordance with earlier findings of improved rhizosphere soil quality parameters coupled with increased nutrient mobilization with significant improvement in nutrient assimilation and grain quality by addition of K fertilizers along with microbial inoculation.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…An increase in protein content, protein yield, and amino acids like lysine, methionine (MTN), and tryptophan, might be due to the fact that crop residue retention improved microbial activity as envisaged by an increase in potassium‐solubilizing bacterial population, soil enzyme activities, and soil microbial biomass that resulted in augmenting the availability of N, P, K, and other micronutrient concentration in soil and also thereby increased absorption and assimilation of N by plants that might have encouraged the translocation of N from vegetative parts to grain which indirectly improved amino acid and protein content. [ 37,44 ] This is in consonance with the earlier findings of Kong, [ 3 ] who reported that nitrate assimilation by wheat increased protein and amino acid profile. Among different K levels, 50% RDK+KSB produced significantly higher protein content, protein yield, and amino acid content over No K and it was statistically nonsignificant with 100 and 150% RDK (Tables 6 and 7), and is in accordance with earlier findings of improved rhizosphere soil quality parameters coupled with increased nutrient mobilization with significant improvement in nutrient assimilation and grain quality by addition of K fertilizers along with microbial inoculation.…”
Section: Resultssupporting
confidence: 83%
“…Similar results of increased microbial activity and concomitant increase in nutrient mobilization and assimilation and thereby improved crop productivity and quality with CR retention, K application, and microbial inoculation were reported earlier. [ 3,45,46 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the major challenges for a global society in the coming decades is to continue to exceed agricultural market pressures while reducing negative impacts on ecosystems and human health (Foley et al 2011). To meet this challenge, a growing number of farmers are implementing "sustainable agriculture" techniques, characterised by employing biofertilisers and crop rotations, as well as reducing degradation of biodiversity, water quality and soil health (Altieri 1995;Kong 2014).…”
Section: Introductionmentioning
confidence: 99%